A photoinduced reaction of perfluoroalkyl halides with 1, 3-diarylprop-2-yn-1-ones catalyzed by DABSO. Issue 9 (7th June 2017) - Li, Yuewen; Lu, Yiye; Mao, Runyu; Li, Zhiming; Wu, Jie
Abstract : The sulfur dioxide surrogate of DABCO·(SO2 )2 is used as an efficient catalyst for the cleavage of the perfluoroalkyl-halogen bond under visible-light irradiation. A plausible mechanism supported by theoretical calculations is proposed. Abstract : The sulfur dioxide surrogate of DABCO·(SO2 )2 is used as an efficient catalyst for the cleavage of the perfluoroalkyl-halogen bond under visible-light irradiation for the first time. This unexpected reaction of perfluoroalkyl halides and 1, 3-diarylprop-2-yn-1-ones catalyzed by DABCO·(SO2 )2 in the presence of visible light proceeds smoothly, leading to 3-fluorinated indenones in good yields. During the reaction process, the cleavage of the perfluoroalkyl-halogen bond and subsequent radical oxidative cyclization are involved under metal-free conditions. A broad reaction scope is observed. Moreover, a plausible mechanism supported by theoretical calculations is proposed.